Pengembangan Media Augmented Reality Terintegrasi Nilai-nilai Islam pada Materi Sistem Saraf untuk Meningkatkan Motivasi dan Hasil Belajar Siswa di SMA Swasta Bandar Setia Ujung - Ayundari, Sella; Manalu, Kartika (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The aim of this research is to integrate Islamic values into the nervous system material and develop augmented reality media to enhance student motivation and learning outcomes in a private high school. The specific objectives are to increase student motivation and learning outcomes through media use and evaluate the suitability of the developed media. This study employs a Research and Development (R&D) approach using the ADDIE model. Fifty-four students participated, including 26 in the experimental group and 28 in the control group. Data were collected through expert validation questionnaires, learning motivation surveys, and tests. Tools used included media validation, learning motivation surveys, and tests. Data analysis involved evaluating media suitability, student motivation, and learning outcomes. Media verification results by validators yielded an average score of 96.01%, classified as